PGF2α and gonadal steroid plasma levels of successful and unsuccessful spawning Piaractus mesopotamicus (Teleostei, Characiformes) females - Kuradomi, Rafael Yutaka [UNESP]; Batlouni, Sergio Ricardo [UNESP] (Springer Nature, 2018)
Gonadal steroid and prostaglandin F2α (PGF2α) plasma levels were evaluated in successfully (SP) and unsuccessfully ovulated (UN) female Piaractus mesopotamicus. Forty-one females were injected with crude carp pituitary extract (0.6 and 5.4 mg kg−1 with a 24-h interval between the doses) and sampled to determine the plasma concentration of 17β-estradiol (E2), 17α-hydroxyprogesterone (17α-OHP), 17α,20β-dihydroxy-4-pregnen-3-one (DHP), PGF2α, and testosterone (T) after each injection (first—A1 and second—A2), and at the time of ovulation for SP and UN. Two clusters were obtained using multivariate analysis: 1—composed of all A1, all A2, and some UN; and 2—composed of all SP and some UN. Median values of E2 plasma levels were similar between clusters; however, plasma levels of T, 17α-OHP, DHP, and PGF2α of cluster 2 (predominantly formed by SP) were higher than those of cluster 1. Since cluster 2 contained all SP and females of this cluster presented higher levels of PGF2α, T, 17α-OHP, and DHP, here we evidently shown in an unprecedented manner that concomitant increased levels of these substances were associated with successful ovulation in this species, but such an increase was not determinant for successful ovulation due to the presence of some UN females in the same cluster 2. These findings highlight the unexplored potential of PGF2α to be used as an accessory tool for inducing successful ovulation for fish farming purposes.
Keywords: Crude carp pituitary extract; Gonadal steroid plasma levels; Multivariate analysis; Pacu; Prostaglandin F2α; Successful spawning